Alquran dan Epistemologi Pengetahuan: Makna Semantik Kata Ra’a, Naẓar dan Baṣar dalam Alquran - Lilik Ummi Kaltsum (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2018)
Epistemology is a philosophical study of the origin, structure, method of validity and the objective of knowledge. It explains the processes and procedures for obtaining knowledge. This study focuses on the sign of Qur'anic language on the process of obtaining knowledge, using semantic analysis. The object of the study is the three-word meaning system in the process of obtaining knowledge in the Qur'an, i.e., ra’a, naẓar and baṣar which translated to 'see something'. This study shows that there are consistences of differences between the three words. Almost all the terms ra’a have the meaning of 'see something with sensory perception.' This meaning is different from the term naẓar that has the meaning of 'see something through the senses and reinforced by reason with any reflections and connections with other objects.' Meanwhile, baṣar has the meaning of 'see something with the heart'. Therefore, based on the study of the three words, the Qur’anic epistemology indicates the importance of senses, reason, and heart in the process of obtaining knowledge.